Captive observations and comparative morphology of Philippine tarsier (Carlito syrichta) in Brgy. Hugpa, Biliran, Biliran a preliminary study - de la Cruz, John O. (John O. de la Cruz, 2014)
A pioneering study of two wild caught tarsiers from Brgy. Hugpa, Biliran, Biliran aimed to identify the subspecies present; to generate taxonomic and morphological data and compare it with the nearest geographically isolated subspecies; to provide initial insights on the locomotive and postural behavior in captivity; and to describe its habitat and sleep sites. Two wild caught tarsiers were studied in captivity. One was placed in a 1x0.5x0.5 m wooden cage and the other was kept in calamansi tree. Gross morphological assessment, cranial and post-cranial measurements were taken from the said specimen. Locomotive and postural behaviors were recorded in every bout and were observed in captivity. The habitat was assessed twice and the sleep sites were marked with Garmin GPS unit. The skull length and body weight, falls within the lower range of values compared to the three subspecies of Philippine tarsier. In captivity, Biliran tarsier utilizes climbing (45.65%) the most, then leaping (43.48%) and infrequently uses quadrupedalism (10.89%) as a means of locomotion. On the other hand, sitting (45.83%) is the most frequently used postural behavior, followed by vertical clinging (25%) and occasionally use standing and cantilevering. Biliran tarsiers inhabit the border of the forest and the local human community. Sleep sites of Biliran tarsiers are categorized into four major types, namely trees with dense understory, bamboos with thick undergrowth, bamboos and dense vegetation consist of grasses and bushes. Further investigation is warranted to ascertain the taxonomic status, locomotive and postural behavior of Biliran tarsier.